Dr. Shay Duvdevani — Deep Plane Facelift — Ramat Gan - Duvdevani, Shay (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Shay Duvdevani, practicing in Ramat Gan, Israel. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002969; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; israel; ramat gan